Loss of CO from the intravascular bed and its impact on the optimised CO-rebreathing method - Prommer, N.; Schmidt, W. (European Journal of Applied Physiology, 2007)
Total haemoglobin mass can be easily measured by applying the optimised CO-rebreathing method (oCOR-method). Prerequisite for its accurate determination is a homogenous CO distribution in the blood and the exact knowledge of the CO volume circulating in the vascular space. The aim of the study was to evaluate the mixing time of CO in the blood after inhaling a CO-bolus and to quantify the CO volume leaving the vascular bed due to diffusion to myoglobin and due to exhalation during processing the oCOR-method. The oCOR-method was also compared to a former commonly used CO-rebreathing procedure. In ten subjects, the time course of carboxy-haemoglobin (HbCO) formation was analysed simultaneously in capillary and venous blood for a period of 15 min after inhaling a CO bolus. The volume of CO diffusing from haemoglobin to myoglobin was calculated via the decrease of HbCO. As part of this decrease is due to CO exhalation, this volume was quantified by collecting the exhaled air in a Douglas bag system. Equal HbCO values in capillary and venous blood were reached at min 6 indicating complete mixing of CO. The loss of CO out of the vascular bed due to exhalation and due to diffusion to myoglobin was 0.32 ± 0.12% min-1 (0.25 ± 0.09 ml min-1) and 0.32 ± 0.18% min-1 (0.24 ± 0.13 ml min-1) of the administered CO volume, respectively. The loss of CO due to exhalation and diffusion to myoglobin is of minor impact. It should, however, be considered by using correction factors to obtain high accuracy when determining total haemoglobin mass.